VALUE-ADDED CREATION IN FINANCIAL PERSPECTIVE BY COLLABORATION OF INTELLECTUAL CAPITAL AND CORPORATE POLICY - Iswari, Hanif Rani; Salim, Ubud; Djazuli, Atim (Universitas Brawijaya, Indonesia, 2019)
This study aimed to analyse and test the creation of optimisation value-added by intellectual capital that collaborates with company policies in the property and real estate sector companies listed on the Indonesia Stock Exchange. The sampling method uses purposive sampling and obtained sample of 15 companies. This study uses path analysis. Intellectual capital is measured by Value Added Intellectual Coefficient (VAIC); Funding decisions are measured by Debt to Equity Ratio (DER); Dividend decisions are measured by Dividend Payout Ratio (DPR); Investment decisions are measured using a combined Investment Opportunity Set (IOS). The value of the firm is measured using Tobin's Q, and the financial performance is measured using Return on Assets (ROA). The results of this study conclude that intellectual capital can improve financial performance but reduce the value of the firm. Funding decisions and dividend decisions reduce financial performance, but investment decisions improve financial performance. Only dividend decisions can increase value of the firm, while investment decisions reduce value of the firm. Even funding decisions do not affect value of the firm. Financial performance has not been able to mediate the flow of value-added creation. From the results of the study, the flow of creating value-added from intellectual capital supported by company policy through the financial performance in property and real estate companies has not been able to increase value of the firm optimally.